2018
DOI: 10.5430/jbar.v7n2p17
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Advertising Appeals on Purchase Intention in Social Media Environment——Analysis of Intermediary Effect Based on Brand Attitude

Abstract: Social media, represented by WeChat and micro-blog, has become an indispensable communication tool for human beings. The social media advertising that extends in this environment has also become the focus of enterprise marketing. Based on the brand attitude as the intermediary variable, this paper studies the influence of advertising appeal on the purchase intention under the socialized media environment, and tries to clarify the influence mechanism between the advertising appeal and the consumer purchase inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 1 publication
(1 reference statement)
2
12
0
1
Order By: Relevance
“…The 'presence' of these streamers in customers' lives influence their buying decisions (Bergel & Brock, 2019;Marsden, 2010). Previous studies argue brand trust and loyalty have played significant intermediary roles in the impact advertising appeals (perceptual and rational) have on purchase intention (He & Qu, 2018;Yang et al, 2015). In a social context, it was argued that rational advertising appeal could propel consumers to a more positive brand attitude toward crisis brands (Yuan et al, 2010).…”
Section: Social Presence and Purchase Behaviormentioning
confidence: 99%
“…The 'presence' of these streamers in customers' lives influence their buying decisions (Bergel & Brock, 2019;Marsden, 2010). Previous studies argue brand trust and loyalty have played significant intermediary roles in the impact advertising appeals (perceptual and rational) have on purchase intention (He & Qu, 2018;Yang et al, 2015). In a social context, it was argued that rational advertising appeal could propel consumers to a more positive brand attitude toward crisis brands (Yuan et al, 2010).…”
Section: Social Presence and Purchase Behaviormentioning
confidence: 99%
“…The finding of the research is that the social media advertising has a significant positive impact on the consumer purchase intention under the intermediate impact based on brand attitude so it is recommended that companies should use information that is more professional in social media advertisement to make their buyer willingness to buy their product. The result of the study showed that humor appeal has a most significant impact on purchase intention, whereas gender appeal also has a positive significant impact on purchase intention (He & Qu, 2018). Moreover, emotional and fear also a have an impact less but significant on purchase intention.…”
Section: Introductionmentioning
confidence: 86%
“…Metode analisis yang digunakan dalam penelitian ini untuk menguji validitas adalah analisis faktor konfirmatori, yaitu melihat nilai factor loadings. Dalam penelitian ini sampel yang digunakan sebanyak 224 responden, dan jika nilai factor loading ≥ 0,40 maka indikator tersebut dapat dinilai valid (Hair et al, 2010). Seluruh item pernyataan yang digunakan untuk mengukur variable Attention Grabbing Details, Celebrity Endorsement, Creative Characteristics, Emotional Appeals dan Purchase Intention.…”
Section: Uji Validitasunclassified